Escaping the Great Recession - Francesco Bianchi; Leonardo Melosi (Federal Reserve Bank of Chicago, 2014)
While high uncertainty is an inherent implication of the economy entering the zero lower bound, deflation is not, because agents are likely to be uncertain about the way policymakers will deal with the large stock of debt arising from a severe recession. We draw this conclusion based on a new-Keynesian model in which the monetary/fiscal policy mix can change over time and zero-lower-bound episodes are recurrent. Given that policymakers' behavior is constrained at the zero lower bound, beliefs about the exit strategy play a key role. Announcing a period of austerity is detrimental in the short run, but it preserves macroeconomic stability in the long run. A large recession can be avoided by abandoning fiscal discipline, but this results in a sharp increase in macroeconomic instability once the economy is out of the recession. Contradictory announcements by the fiscal and monetary authorities can lead to high inflation and large output losses. The policy trade-off can be resolved by committing to inflate away only the portion of debt resulting from an unusually large recession.
Keywords: E31; E52; E62; E63; D83; 330; policy uncertainty; macroeconomic uncertainty; Markov-switching models; shock-specific policy rules; zero lower bound